2018
DOI: 10.3390/su10082945
|View full text |Cite
|
Sign up to set email alerts
|

Control Dust Pollution on Construction Sites: What Governments Do in China?

Abstract: Dust pollution is a key issue that contractors ought to address in the sphere of sustainable construction. Governments on behalf of the public assume part of the responsibilities for minimizing dust emissions on construction sites. However, the measures that are useful for governments to fulfill such a responsibility have not been explored explicitly in previous studies. The aim of this research is to map out China's practices in this area with the intention of filling the knowledge gap. Using a combination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…This is also in line with the Czech cultural tradition of mushroom picking (Šišák et al 2016 ; Ministry of Agriculture 2019 ; Wolfslehner et al 2019 ; Purwestri et al 2020 ; Riedl et al 2020 ) as well as traditional Chinese exercise, which has a deep tradition and makes a connection between humans and nature (Jiang and Zou 2013 ; Guo et al 2014 ; Wang et al 2021 ). Geographical location contributes to the distribution of sandstorm and industrial conditions, which also bring dust and pollution issues to the fore in China more than in the Czech Republic (Xin-fa et al 2001 ; Xing et al 2018 ). However, in line with the ideas of Dou et al ( 2020 ), it can be concluded that the forest cultural services are directly influenced by cultural habits.…”
Section: Discussionmentioning
confidence: 99%
“…This is also in line with the Czech cultural tradition of mushroom picking (Šišák et al 2016 ; Ministry of Agriculture 2019 ; Wolfslehner et al 2019 ; Purwestri et al 2020 ; Riedl et al 2020 ) as well as traditional Chinese exercise, which has a deep tradition and makes a connection between humans and nature (Jiang and Zou 2013 ; Guo et al 2014 ; Wang et al 2021 ). Geographical location contributes to the distribution of sandstorm and industrial conditions, which also bring dust and pollution issues to the fore in China more than in the Czech Republic (Xin-fa et al 2001 ; Xing et al 2018 ). However, in line with the ideas of Dou et al ( 2020 ), it can be concluded that the forest cultural services are directly influenced by cultural habits.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly lesser quantities are the result of VOC, NO 2 and C 6 H 6 . The emission of PM 10 is one order of magnitude less with respect to CO and NO x , but it produces the most perceived and undesired effects of the construction process in the interested communities [34,35].…”
Section: Resultsmentioning
confidence: 99%
“…To avoid negative impacts of construction dust pollution, regulatory and engineering control measures have been proposed by most of these studies. Very few studies have investigated the way to avoid or reduce the generation of dust [21,[45][46][47]. A summary of the solutions proposed by past studies is presented in Table 1, classified by three main categories.…”
Section: Dust Pollution Control On Sitesmentioning
confidence: 99%